2022
DOI: 10.53703/001c.32489
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Entrepreneurship Intentions: The Role of Entrepreneurship Education

Abstract: To foster economic development, entrepreneurship is a crucial pillar. Young people and especially students are potential entrepreneurs, whereas education is crucial to promote capabilities and to pursue intentions. In this research we study the importance and effect of the personal characteristics of students, the inherent psychological factors, and the influence of education and training to promote entrepreneurial intentions. From our sample of 1750 students, we conclude about the importance of entrepreneuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Youth and particularly students are potential entrepreneurs, whereas education is crucial to promote capabilities (Porfírio, Carrilho, Jardim, & Wittberg, 2022). The young students needs motivation, and that education might support their intention (Melia Astiana, Maya Malinda, Anny Nurbasari, 2021), as much as entrepreneurship education (EE) has progressively been introduced as a school-wide approach to encourage an entrepreneurial mindset across various educational levels (Baggen, Lans, & Gulikers, 2022).…”
Section: Entrepreneurial Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth and particularly students are potential entrepreneurs, whereas education is crucial to promote capabilities (Porfírio, Carrilho, Jardim, & Wittberg, 2022). The young students needs motivation, and that education might support their intention (Melia Astiana, Maya Malinda, Anny Nurbasari, 2021), as much as entrepreneurship education (EE) has progressively been introduced as a school-wide approach to encourage an entrepreneurial mindset across various educational levels (Baggen, Lans, & Gulikers, 2022).…”
Section: Entrepreneurial Educationmentioning
confidence: 99%
“…The analysis allowed to add new information related to entrepreneurial education, with the collected data pointing in two different directions. Firstly, entrepreneurship educational programs may positively influence entrepreneurship intentions (Porfírio et al, 2022), management students point to the importance of entrepreneurial education, as advocated by (Bae et al, 2014), although the same is not true for the general management students, since despite having this knowledge it was not possible to find a higher percentage of students with entrepreneurial intention.…”
Section: Cluster 4 -Entrepreneurial Educationmentioning
confidence: 99%
“…For instance, in Turkey, the study by Mohanty et al (2021) showed that the youths are participating in entrepreneurship due to the skills they acquire during the learning process. Similarly, the study by Porfírio et al (2022) revealed that entrepreneurship education permits students to develop various aspects of entrepreneurial selfefficacy like modeling, mastery experience, social persuasion, and self-judgment of psychological entrepreneurship-related characteristics. The findings of the studies from Turkey and Spain signify that if students participated in the IGAs through learning by doing in the public secondary schools help to gain practical entrepreneurial skills that suit their life after the school circle.…”
Section: Introductionmentioning
confidence: 98%
“…Over the past few years, the importance of entrepreneurship has grown significantly (Porfírio et al , 2022); hence, most of the countries have started focusing on developing and strengthening entrepreneurial ventures since governments are not able to deliver financial stability to their populations solely on their own (Hossain et al , 2023). Existing resources in developing countries may not be adequate to deal with increased job requirements due to increasing population and consumption.…”
Section: Introductionmentioning
confidence: 99%